1986
DOI: 10.1063/1.337785
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure and formation mechanism of drawing-induced absorption at 630 nm in silica optical fibers

Abstract: This paper presents a study on drawing condition dependences of optical absorption at 630 nm and nonbridging oxygen hole centers (NBOHCs) in optical fibers drawn from low-OH-content synthetic silica glass. The intensity of the 630-nm absorption is proportional to the NBOHC concentration, and the value of the oscillator strength for the NBOHC is 4.2×10−4, which nearly equals the theoretical values. These results confirm that the 630-nm absorption is due to the NBOHCs in low-OH-content silica glass. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 15 publications
1
24
0
1
Order By: Relevance
“…The structural defects thereby produced within the fibre core represent the main basis for TL radiation dosimeter applications. Over and above the defects generated by the dopant impurities in the core, additional defects are induced in the optical fibre core during the fibre drawing process, influenced by fibre tension and the neck-down shearing effect (Friebele et al, 1976;Hanafusa et al, 1987;Hibino and Hanafusa 1986;Lee et al, 1998). These defects provide additional dose detection sensitivity of optical fibres, a situation not observed in sol-gel based or other forms of glass dosimeter.…”
Section: Introductionmentioning
confidence: 93%
“…The structural defects thereby produced within the fibre core represent the main basis for TL radiation dosimeter applications. Over and above the defects generated by the dopant impurities in the core, additional defects are induced in the optical fibre core during the fibre drawing process, influenced by fibre tension and the neck-down shearing effect (Friebele et al, 1976;Hanafusa et al, 1987;Hibino and Hanafusa 1986;Lee et al, 1998). These defects provide additional dose detection sensitivity of optical fibres, a situation not observed in sol-gel based or other forms of glass dosimeter.…”
Section: Introductionmentioning
confidence: 93%
“…It is believed that higher temperatures stimulate the dissociation of Si-F bonds, which induce ODC(II)s and F 2 molecules [8]. Higher drawing speeds enhance the formation of Ôdrawing induced defectsÕ, which correspond to a pair formation of E 0 center and NBOHC via bond-breaking of Si-OSi [9,10].…”
Section: Transmission Of Fluorine Doped Silica Fibersmentioning
confidence: 99%
“…Furthermore, Photo Luminescence (PL) measurements have demonstrated that some diamagnetic defects such as the Oxygen Deficiency Centre (ODC) may act as defect precursors for paramagnetic defects [7]. These colour defects have been associated with optical absorption bands at short wavelengths below 700 nm [8] and may already be generated during the fiber manufacturing process [9], [10].…”
Section: Introductionmentioning
confidence: 99%